ZIKV Infection Induces an Inflammatory Response but Fails to Activate Types I, II, and III IFN Response in Human PBMC - Francesca Colavita; Veronica Bordoni; Claudia Caglioti; Mirella Biava; Concetta Castilletti; Licia Bordi; Serena Quartu; Marco Iannetta; Giuseppe Ippolito; Chiara Agrati; Maria Rosaria Capobianchi; Eleonora Lalle (Mediators of Inflammation)
The recent epidemic in the Americas caused by Zika virus (ZIKV), Asian lineage, spurred the research towards a better understanding of how ZIKV infection affects the host immune response. The aim of this study was to evaluate the effects of Asian and East African ZIKV strain infection on the induction of IFN and proinflammatory and Th2 cytokines in human PBMC. We reported a slight modulation of type II IFN in PBMC exposed to Asian strain, but not to African strain, and a complete lack of type I and III IFN induction by both strains, suggesting the ability of ZIKV to evade the IFN system not only inhibiting the antiviral IFN response but also IFN production. Moreover, we highlighted a polyfunctional immune activation only in PBMC exposed to Asian strain, due to the induction of an inflammatory profile (IL-6, IL-8) and of a Th9 (IL-9) response. Overall, our data show a different ability of the ZIKV Asian strain, with respect to the African strain, to activate host immune response that may have pathogenetic implications for virus spread in vivo, including mother-to-child transmission and induction of severe fetal complications, as birth defects and neurological disorders.